PELATIHAN MEDIA BELAJAR BERBASIS ONLINE DI ERA PANDEMI - Kartono Pinaryanto; Anastasia Rita Widiarti; Haris Sriwindono; Ridowati Gunawan; Hari Suparwito; Sri Hartati Wijono; Rosalia Arum Kumalasanti; Wiwien Widyastuti (Universitas Sanata Dharma, 2022)
The education sector is one of the areas that has been most affected by the COVID-19 pandemic. Schools, which normally hold offline meetings, must now take place online. With this pandemic, the teaching process must be